Identifying Influenza Viruses with Resequencing Microarrays - Zheng Wang; Luke T. Daum; Gary J. Vora; David Metzgar; Elizabeth A. Walter; Linda C. Canas; Anthony P. Malanoski; Baochuan Lin; David A. Stenger (Emerging Infectious Diseases, 2006)
Identification of genetic variations of influenza viruses is essential for epidemic and pandemic outbreak surveillance and determination of vaccine strain selection. In this study, we combined a random amplification strategy with high-density resequencing microarray technology to demonstrate simultaneous detection and sequence-based typing of 25 geographically distributed human influenza virus strains collected in 2004 and 2005. In addition to identification, this method provided primary sequence information, which suggested that distinct lineages of influenza viruses co-circulated during the 2004–2005 season, and simultaneously identified and typed all component strains of the trivalent FluMist intranasal vaccine. The results demonstrate a novel, timely, and unbiased method for the molecular epidemiologic surveillance of influenza viruses.